2012
DOI: 10.1016/j.jvs.2011.05.092
|View full text |Cite
|
Sign up to set email alerts
|

The controversy of managing calf vein thrombosis

Abstract: No study of strong methodology could be found to resolve the controversy of optimal treatment of C-DVT. Given the risks of propagation, PE, and recurrence, the option of doing nothing should be considered unacceptable. In the absence of strong evidence to support anticoagulation over imaging surveillance with selective anticoagulation, either method of managing calf DVT must remain as current acceptable standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(85 citation statements)
references
References 61 publications
0
82
0
3
Order By: Relevance
“…Only a few studies, of different design (retrospective or prospective) and in different clinical settings (post-surgery, in-or outpatient, thrombosis limited to the deep muscle veins), have addressed the issue of management in patients with confirmed IDDVT (see a recent review by Masuda 46 ), often with inconsistent results. A recent meta-analysis of available controlled studies on anticoagulation (at least 1 month of a therapeutically dosed anticoagulant drug) in patients with IDDVT included only 8 studies (most of them judged to be of poor methodological quality) and concluded that anticoagulation therapy may reduce the incidence of PE and thrombus propagation, whereas bleeding events (that were reported sparsely in the studies) seemed to favor controls.…”
Section: What Is Done In Studies and In Clinical Practicementioning
confidence: 99%
“…Only a few studies, of different design (retrospective or prospective) and in different clinical settings (post-surgery, in-or outpatient, thrombosis limited to the deep muscle veins), have addressed the issue of management in patients with confirmed IDDVT (see a recent review by Masuda 46 ), often with inconsistent results. A recent meta-analysis of available controlled studies on anticoagulation (at least 1 month of a therapeutically dosed anticoagulant drug) in patients with IDDVT included only 8 studies (most of them judged to be of poor methodological quality) and concluded that anticoagulation therapy may reduce the incidence of PE and thrombus propagation, whereas bleeding events (that were reported sparsely in the studies) seemed to favor controls.…”
Section: What Is Done In Studies and In Clinical Practicementioning
confidence: 99%
“…However, controversy exists regarding optimal management of DVT in the calves. 2 Given the risk of propagation, pulmonary embolism and recurrence, doing nothing is unacceptable. A systematic review of 6 randomized controlled trials (RCTs) and 25 observational studies concluded that either observation with elastic compression stockings and serial imaging surveillance, or anticoagulation therapy are acceptable management options.…”
Section: Management Of Vtementioning
confidence: 99%
“…A systematic review of 6 randomized controlled trials (RCTs) and 25 observational studies concluded that either observation with elastic compression stockings and serial imaging surveillance, or anticoagulation therapy are acceptable management options. 2 When anticoagulation is determined necessary, a 2016 guideline recommended direct anti coagulants, such as oral riva roxaban, based on six RCTs and meta-analysis. 3 Determining appropriate treatment requires consideration of provoking factors and patient preferences.…”
Section: Management Of Vtementioning
confidence: 99%
“…There is a risk of PE resulting from calf DVT either because of propagation or embolism from the calf itself. There are no studies of the risk of PE in stroke patients, but in other patients with calf DVT, the risk of symptomatic PE is up to 1 % and asymptomatic PE up to 6 % [ 36 ].…”
Section: Below-knee Distal or Calf Dvtmentioning
confidence: 99%